Low utility of the H-Score and HLH-2004 criteria to identify patients with secondary hemophagocytic lymphohistiocytosis after CAR-T cell therapy for relapsed/refractory diffuse large B-Cell lymphoma. Issue 6 (12th May 2022) - Kim, Dong Won; Bukhari, Ali; Lutfi, Forat; Zafforoni, Facundo; Merechi, Fikru; Mustafa Ali, Moaath K.; Gottlieb, David; Lee, Seung T.; Kocoglu, Mehmet H.; Hardy, Nancy M.; Yared, Jean; Rapoport, Aaron P.; et al.
Abstract: Secondary hemophagocytic lymphohistiocytosis (HLH) is a life-threatening immune dysregulation disorder. Use of chimeric antigen receptor T-cell therapy (CAR-T) is associated with cytokine release syndrome (CRS), Immune Effector Cell Associated Neurotoxicity Syndrome (ICANS) and secondary HLH. However, application of HLH scoring systems (H-score, HLH-2004 criteria) are not validated in this setting. We analyzed the utility of applying the H-score and the HLH-2004 criteria to identify patients with possible HLH post-CAR-T for Relapsed/Refractory Diffuse Large B-cell Lymphoma. Only two of four patients with post CAR-T HLH met five or more of the diagnostic criteria for HLH by HLH 2004 criteria. In contrast all four post CAR-T HLH patients had a high H-score (>169); however, an additional ten patients that did not have HLH also had a high H-score. Thus, in this patient population, both scoring systems were demonstrated to have low prognostic significance in differentiating between high grade CRS and HLH.